MOONWALKING: TRACING REDDITORS’ DIGITAL MEMORY WORK ON MICHAEL JACKSON - Esteve Del Valle, Marc; Smit, Rik (AoIR Selected Papers of Internet Research, 2020)
This paper investigates the memory work concerning Michael Jackson on the social content aggregation site Reddit. By means of their posts, comments and replies, people contributing to this site—Redditors—enter into a process we call the dynamics of mnemonic stabilization. This is a collaborative process in which networked individuals share their memories about, in this case, Michael Jackson. This process resembles Jackson’s dance technique called moonwalking: Redditors seem to go back in time, but they continually alter how Jackson is remembered and forgotten, depending on the (personal) context of the present and an imagined future. These theoretical observations are empirically assessed by a content analysis of mnemonic comments and replies (N=917) posted on the subreddit /r/MichaelJackson between June 25, 2009, and December 31, 2018. This revealed that most posts with a mnemonic dimension focus on personal memories of Michael Jackson’s music, performances and (perceived) positive characteristics